2023
DOI: 10.3390/ijms24021392
|View full text |Cite
|
Sign up to set email alerts
|

Tailored PGE2 Immunomodulation of moDCs by Nano-Encapsulated EP2/EP4 Antagonists

Abstract: Prostaglandin E2 (PGE2) is an important maturation mediator for dendritic cells (DCs). However, increased PGE2 levels in the tumor exert immunosuppressive effects on DCs by signaling through two E-Prostanoid (EP) receptors: EP2 and EP4. Blocking EP-receptor signaling of PGE2 with antagonists is currently being investigated for clinical applications to enhance anti-tumor immunity. In this study, we investigated a new delivery approach by encapsulating EP2/EP4 antagonists in polymeric nanoparticles. The nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
1
2
0
1
Order By: Relevance
“…The expression of co-stimulatory molecules is a hallmark of DC maturation. In moDCs, addition of PGE2 during maturation has been demonstrated to upregulate co-stimulatory markers including CD80, CD86, CD83, and HLA-DR [15,20,23,26]. In line with these reports, we observed that MC+PGE2 upregulated these markers also on human cDC2s.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The expression of co-stimulatory molecules is a hallmark of DC maturation. In moDCs, addition of PGE2 during maturation has been demonstrated to upregulate co-stimulatory markers including CD80, CD86, CD83, and HLA-DR [15,20,23,26]. In line with these reports, we observed that MC+PGE2 upregulated these markers also on human cDC2s.…”
Section: Discussionsupporting
confidence: 89%
“…3A). Specifically, we employed the aEP2 AH6809 and the aEP4 L161-982, which prevent EP specific PGE2 binding and have previously been used on immune cells [10,15,26,35,48]. MC+PGE2 resulted in the upregulation of CD80, CD83, CD86, HLA-DR, and the co-inhibitory molecule PDL-1 on cDC2s (Fig.…”
Section: Pge2 Signaling Via Ep4 Modulates the Upregulation Of Maturat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Як було продемонстровано J. Bоdder і співавт. [72], блокування шляхів сигналювання, опосередкованих через рецептори до ПГЕ2 за допомогою антагоністів до цих рецепторів, запобігало виникненню ПГЕ2-індукованої імуносупресорної активності ДК. W. Zhang і співавт.…”
Section: способи стимуляції функціонального дозрівання дендритних клітинunclassified